A DFT Investigation of Alkali Metal Doping for the Tuning of Circumcoronene’s Electronic Properties - Shwayyea, Noora B; Khammat, Mohammed A; Khudhair, Alaa M. (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
In this study, the electronic and chemical reactivity properties of circumcoronene (CC), a graphene analog with significant potential for nanoelectronic applications, are examined in relation to the contamination of sodium and potassium. The research analyzes seven distinct structural configurations that involve a variety of doping schemes using density functional theory (DFT) at the B3LYP/6-31G level of theory. Energy gaps, Fermi levels, dipole moments, HOMO, LUMO, and density of states (DOS) are assessed as critical electronic parameters. The results indicate that alkali metal doping consistently reduces the band gap and improves conductivity. The most pronounced effect is seen in co-doping (Na and K), which reduces the band gap to 1.012 eV and increases the dipole moment and Fermi level. Enhanced reactivity and tunability were confirmed by the calculation of chemical indices, including ionization potential, electron affinity, hardness, softness, electronegativity, and electrophilicity, during the doping process. These results underscore the efficacy of Na and K incorporation as a strategic approach to alter the optoelectronic properties of circumcoronene, thereby confirming its suitability for future applications in advanced nanoelectronics devices.